Integrin-Mediated Tumorigenesis and Its Therapeutic Applications - Li, Qingling; Lan, Ting; Xie, Jian; Lu, Youguang; Zheng, Dali; Su, Bohua (Frontiers in Oncology, 2022)
Integrins, a family of adhesion molecules generally exist on the cell surface, are essential for regulating cell growth and its function. As a bi-directional signaling molecule, they mediate cell-cell and cell-extracellular matrix interaction. The recognitions of their key roles in many human pathologies, including autoimmunity, thrombosis and neoplasia, have revealed their great potential as a therapeutic target. This paper focuses on the activation of integrins, the role of integrins in tumorigenesis and progression, and advances of integrin-dependent tumor therapeutics in recent years. It is expected that understanding function and signaling transmission will fully exploit potentialities of integrin as a novel target for tumors.